ANALISIS KEPUTUSAN KONSUMEN JASA BMT MANDIRI SEJAHTERA JAWA TIMUR - Martha Laila Arisandra; Yuanis Yuanis; Estri Purwani Rahayu (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
This study aims to determine the level of satisfaction of members of the cooperative towards the services of employees of the BMT Mandiri Sejahtera Jawa Timur . This research includes case study research using a qualitative approach. The subjects of this study were members of the BMT Mandiri Sejahtera Jawa Timur. The subjects of this study were members of the BMT Mandiri Sejahtera Jawa Timur. The data collection technique is by interview. In testing the validity of the data, the researcher used source triangulation. The data analysis techniques used are Data Reduction, Data Presentation, and Conclusions and Verification. The results showed that the level of satisfaction of the members of the BMT Mandiri Sejahtera Jawa Timur with the services of thevBMT Mandiri Sejahtera Jawa Timur proposed by the cooperative members was satisfied. As for the level of satisfaction of members of the BMT Mandiri Sejahtera Jawa Timur, the first thing that must be possessed to provide the best service is a good attitude, being friendly to cooperative members and polite to service users. These three attitudes can make customers feel comfortable and happy so they have the opportunity to come back again.